STRATEGI PEMBELAJARAN AKTIF KNOWLEDGE SHARING DALAM KEMAMPUAN PSIKOMOTORIK PADA MATA PELAJARAN FIQIH (Studi Pada Siswa MTs Al-Washliyah Gedung Johor) - Br. Padang, Nurul Rahena (Fakultas Agama Islam, 2020)
The knowledge sharing learning strategy applied by teachers at MTs Al-Washliyah, Johor Building illustrates that students 'psychomotor abilities are still low, especially in fiqh lessons, according to the author because the learning strategies applied so far are still conventional, so that students' psychomotor abilities are weak, therefore To improve students 'psychomotor abilities, it is necessary to apply Active Knowledge Sharing learning strategies. Because Active Knowledge Sharing learning can improve students' psychomotor abilities. The problem in this study is how to implement the Active Knowledge Sharing learning strategy in fiqh lessons at MTs Gedung Johor. What is the psychomotor ability of MTs Al-Washliyah building Johor students in learning Fiqh. Inhibiting and supporting factors in the application of Active Knowledge Sharing learning strategies to students' psychomotor abilities at MTs Al-Washliyah Medan Johor. The results of this study indicate that the active knowledge sharing learning strategy is a learning strategy by asking questions at the beginning of the lesson by the teacher and providing opportunities for students to share, exchange ideas, exchange opinions and exchange knowledge to find the right answer and then answer it by the students. The psychomotor abilities of students are increasing with the implementation of active knowledge sharing, these psychomotor abilities are in accordance with the material being taught, namely an increase in the ability of students to perform ablution and prayer. There are several obstacles in implementing Active knowledge sharing learning strategies, including the lack of time available, differences in students' different thinking abilities. In terms of overcoming this requires patience and the need for motivation from the teacher and from among students.